Association Between Typhoid and Paratyphoid Fever with ABO Blood Group among Patients Attending Raparin Pediatric Hospital in Erbil - Khanzad Hadi Alchawishli; Sadiya Abdulla Palpitany; Banaz Sadiq Smail; Shukir Salem Hassan (Diyala Journal of Medicine, 2019)
Background: The ABO blood groups and Rhesus factor are different in their susceptibility and resistance to various diseases. The role of ABO blood group has long been a subject of investigation and debate. Typhoid and paratyphoid disease is commonly encountered a systemic disease caused by gram negative bacteria Salmonella typhi and Salmonella paratyphi. Because of the presence of favorable predisposing factors for transmission of typhoid disease among children in Kurdistan.